Ocean acidification decreases plankton respiration : evidence from a mesocosm experiment - Spilling, Kristian; Paul, Allanah J.; Virkkala, Niklas; Hastings, Tom; Lischka, Silke; Stuhr, Annegret; Bermudez, Rafael; Czerny, Jan; Boxhammer, Tim; Schulz, Kai G.; Ludwig, Andrea; Riebesell, Ulf (Biogeosciences, 2016)
Anthropogenic carbon dioxide (CO2) emissions are reducing the pH in the world's oceans. The plankton community is a key component driving biogeochemical fluxes, and the effect of increased CO2 on plankton is critical for understanding the ramifications of ocean acidification on global carbon fluxes. We determined the plankton community composition and measured primary production, respiration rates and carbon export (defined here as carbon sinking out of a shallow, coastal area) during an ocean acidification experiment. Mesocosms (similar to 55 m(3)) were set up in the Baltic Sea with a gradient of CO2 levels initially ranging from ambient (similar to 240 mu atm), used as control, to high CO2 (up to similar to 1330 mu atm). The phytoplankton community was dominated by dinoflagellates, diatoms, cyanobacteria and chlorophytes, and the zooplankton community by protozoans, heterotrophic dinoflagellates and cladocerans. The plankton community composition was relatively homogenous between treatments. Community respiration rates were lower at high CO2 levels. The carbon-normalized respiration was approximately 40% lower in the high-CO2 environment compared with the controls during the latter phase of the experiment. We did not, however, detect any effect of increased CO2 on primary production. This could be due to measurement uncertainty, as the measured total particular carbon (TPC) and combined results presented in this special issue suggest that the reduced respiration rate translated into higher net carbon fixation. The percent carbon derived from microscopy counts (both phyto- and zooplankton), of the measured total particular carbon (TPC), decreased from similar to 26% at t0 to similar to 8% at t31, probably driven by a shift towards smaller plankton (<4 mu m) not enumerated by microscopy. Our results suggest that reduced respiration leads to increased net carbon fixation at high CO2. However, the increased primary production did not translate into increased carbon export, and consequently did not work as a ...